ON SOME DOUBLE INTEGRALS INVOLVING -FUNCTION OF TWO VARIABLES AND SPHEROIDAL FUNCTIONS - Singh, Yashwant; Joshi, Laxmi (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The present paper evaluates certain double integrals involving -function of two variables [21] and Spherodial functions [23]. These double integrals are of most general character known so far and can be suitably specialized to yield a number of known or new integral formulae of much interest to mathematical analysis which are likely to prove quite useful to solve some typical boundary value problems.Â 